Pharmacokinetic analysis of inhaled salmeterol in asthma patients: Evidence from two dry powder inhalers - Soulele, Konstantina; Macheras, Panos; Karalis, Vangelis (BIOPHARMACEUTICS & DRUG DISPOSITION, 2017)
Salmeterol (SAL) is a long-acting beta 2-adrenergic agonist, which is widely used in the therapy of asthma. The aim of this study was to investigate the pharmacokinetics (PK) of inhaled salmeterol in asthma patients using two different dry powder inhalers. This analysis was based on data from 45 subjects who participated in a two-sequence, four-period crossover bioequivalence (BE) study after single administration of the test (T) and reference (R) products. In order to mimic more closely the real treatment conditions, activated charcoal was not co-administered. Plasma concentration-time (C-t) data were initially analysed using classic non-compartmental PK approaches, while the main objective of the study was to apply population PK modeling. The relative fraction of the dose absorbed via the lungs (R-L) was set as a parameter in the structural model. The plasma C-t profiles of salmeterol showed a biphasic time course indicating a parallel pulmonary and gastrointestinal (GI) absorption. A two-compartment disposition model with first order absorption from the GI and very rapid absorption from lungs (like an i.v. bolus) was found to describe successfully the C-t profiles of salmeterol. The estimated R-L value was 13% suggesting a high gut deposition of inhaled salmeterol. Women were found to exert less capability to eliminate salmeterol than men, while body weight (in allometric form) was found to be an important covariate on the peripheral volume of distribution.
Keywords: dry powder inhalers; parallel absorption; population pharmacokinetics; salmeterol xinafoate